Using PDCA as a General Framework for Teaching and Evaluating the Learning of Software Engineering Disciplines - Mergen, Sérgio; Kepler, Fábio; Silva, João Pablo S. da; Cera, Márcia C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2013: Anais do IX Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2013.5711, 2013)
Software engineering disciplines need to be taught in contexts as diverse as undergraduate courses and large corporations training programs. A primary challenge in teaching such disciplines, in any context, is to quickly and effectively evaluate the students learning and measure their strengths and weaknesses. Another challenge is to make students of different instances of a discipline end up with the same basic foundations, turning knowledge independent of the instructor. To overcome these challenges we propose an approach for software engineering teaching based on adapted PDCA cycles and checklists as instruments of evaluation. We also report a case study which shows the implementation of this approach in teaching a first year undergraduate software engineering course. With a careful definition of checklists, the use of the adapted version of PDCA as a methodology for software engineering teaching is promising, allowing an efficient form of evaluation.